Perbandingan Visualisasi Data Customer Churn: Python, Tableau, dan Power BI - HAEKAL, RAGYL (JUSS (Jurnal Sains dan Sistem Informasi), 2023)
This study discusses a comparison of customer churn data visualization using Python, Tableau, and Power BI in the banking industry. Churning or switching customers is a major concern for banking companies because it can have a negative impact on the company's revenue and reputation. Data visualization is an effective approach to analyzing customer churn, turning raw data into informative visuals. Python is a multipurpose programming language that can generate data visualizations with the help of libraries such as Pandas and Matplotlib. Tableau is a data visualization software with an intuitive interface that enables the creation of attractive interactive visualizations. Power BI is a data visualization tool that has integrations with other Microsoft business tools. This study uses bank customer datasets and performs data processing and visualization using these three platforms. The conclusion of this research is that the three platforms have their respective advantages and disadvantages, and the selection of the most appropriate platform depends on the needs of the analysis, the user's level of expertise, and the availability of existing resources and infrastructure.